2013
DOI: 10.7860/jcdr/2013/5524.2947
|View full text |Cite
|
Sign up to set email alerts
|

The Prospect of Serum Magnesium and an Electrolyte Panel as an Adjuvant Cardiac Biomarker in the Management of Acute Myocardial Infarction

Abstract: Background: Ischemic heart disease accounts 12.2% deaths worldwide. Serum magnesium (Mg+) status is often ignored in Acute Myocardial Infarction (AMI). Studies showed alterations in the levels of serum electrolytes including magnesium in AMI. Aim:To evaluate serum Mg+ and other electrolytes as adjuvant markers in the diagnosis of AMI. Design and Settings:Case control study was conducted in South Indian male population with AMI within six hours of onset of symptoms. Patients and Methods:Study includes sixty pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…20 Serum magnesium was determined using flame atomic absorption spectrophotometer; (AA-630-12) (Schimadzu Europe, GmbH, Albert-Hahn-Strasse 6-10, Germany. 21 The reference range of Mg was 1.6-2.6 mg/dl.…”
Section: Ethical Aspectsmentioning
confidence: 99%
“…20 Serum magnesium was determined using flame atomic absorption spectrophotometer; (AA-630-12) (Schimadzu Europe, GmbH, Albert-Hahn-Strasse 6-10, Germany. 21 The reference range of Mg was 1.6-2.6 mg/dl.…”
Section: Ethical Aspectsmentioning
confidence: 99%
“…Chloride ion had no significant value in this study as similar as to Mati E et al, study. 10,11 The decrease in potassium level is common in hypertensive patients of AMI. Present study showed that there is increase of potassium level in hypertensive patients when compared with non-hypertensive p-value = 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…However, cardiac arrest, cardiac failure, myocardial infarction, Parkinson's syndrome and prostate enlargement were detected for the first time when the signal detection methods were used. The exact mechanism of heart disease by imipenem is not clear, but electrolyte exchange, a known ADR of imipenem, is a significant adjuvant marker of acute myocardial infarction 22. Furthermore, seizure, a serious ADR of imipenem, is associated with an increased risk of sudden cardiac death,23 and bradycardia or tachycardia is included in the drug label information in some countries.…”
Section: Discussionmentioning
confidence: 99%